EnROL: A multicentre randomised trial of conventional versus laparoscopic surgery for colorectal cancer within an enhanced recovery programme - Kennedy, Robin H (BioMed Central, 2012)
BACKGROUND: During the last two decades the use of laparoscopic resection and a multimodal approach known as an enhanced recovery programme, have been major changes in colorectal perioperative care. Clinical outcome improves using laparoscopic surgery to resect colorectal cancer but until recently no multicentre trial evidence had been reported regarding whether the benefits of laparoscopy still exist when open surgery is optimized within an enhanced recovery programme. The EnROL trial (Enhanced Recovery Open versus Laparoscopic) examines the hypothesis that laparoscopic surgery within an enhanced recovery programme will provide superior postoperative outcomes when compared to conventional open resection of colorectal cancer within the same programme. METHODS/DESIGN: EnROL is a phase III, multicentre, randomised trial of laparoscopic versus open resection of colon and rectal cancer with blinding of patients and outcome observers to the treatment allocation for the first 7 days post-operatively, or until discharge if earlier. 202 patients will be recruited at approximately 12 UK hospitals and randomised using minimization at a central computer system in a 1:1 ratio. Recruiting surgeons will previously have performed >100 laparoscopic colorectal resections and >50 open total mesorectal excisions to minimize conversion. Eligible patients are those suitable for elective resection using either technique. Excluded patients include: those with acute intestinal obstruction and patients in whom conversion from laparoscopic to open procedure is likely. The primary outcome is physical fatigue as measured by the physical fatigue domain of the multidimensional fatigue inventory 20 (MFI-20) with secondary outcomes including postoperative hospital stay; complications; reoperation and readmission; quality of life indicators; cosmetic assessments; standardized performance indicators; health economic analysis; the other four domains of the MFI-20. Pathological assessment of surgical quality will also be undertaken and compliance with the enhanced recovery programme will be recorded for all patients. DISCUSSION: Should this trial demonstrate that laparoscopic surgery confers a significant clinical and/or health economic benefit this will further support the transition to this type of surgery, with implications for the training of surgeons and resource allocation. TRIAL REGISTRATION: ISRCTN48516968.